The Influence Of Financial Literacy, Financial Technology (Fintech) And Social Environment On Financial Behavior Of Students Of The Faculty Of Economics, Class 2022-2023 - Nurul Aidiatul Fitri; Sulkiah Sulkiah (UNIVED Press, 2025)
This research aims to examine the influence of financial literacy, financial technology (FinTech), and the social environment on the financial behavior of students at the Faculty of Economics, Gunung Rinjani University, class of 2022-2023. With the increasing relevance of financial behavior due to technological advancements and rising living costs, this study explores how students manage their finances, considering the impact of financial literacy, FinTech adoption, and social influences. The study employed a quantitative approach, using questionnaires distributed to 66 students. Data analysis was conducted using SmartPLS. The findings reveal that both financial literacy and the adoption of FinTech positively and significantly influence students' financial behavior. In contrast, the social environment did not exhibit a significant effect on financial behavior. These results suggest that improving financial literacy and encouraging the responsible use of FinTech could enhance students' financial decision-making and overall financial well-being. This study highlights the importance of educating students on financial management skills and the potential role of technology in fostering better financial behavior.